Vitamin D Level and Activities of Daily Living in Octogenarians: Cross-Sectional Study - Alekna, Vidmantas; Kilaite, Justina; Mastaviciute, Asta; Tamulaitiene, Marija (Frontiers in Endocrinology, 2018)
Introduction Despite the growing number of octogenarians, little is known about their vitamin D status and activities of daily living (ADL) relations. Objective The aim of this study was to investigate peculiarities of vitamin D and ADL and to assess their relations in octogenarians. Methods A cross-sectional study was performed at the National Osteoporosis Centre located in Vilnius, Lithuania. Community-dwelling ambulatory persons aged ≥80 years were included. Current users of vitamin D supplements were excluded. Total 25 hydroxyvitamin D concentration in serum was measured with Cobas E411. Functional status was assessed by Katz ADL and the Lawton Instrumental Activities of Daily Living (IADL) scales. Subjects were divided into three groups according to age and into two groups according to vitamin D level. One-way analysis of variance with post hoc test was used to determine between-group comparisons. Associations between vitamin D and ADL score, and IADL score were assessed using Spearman’s correlation. Results The study was performed on 153 octogenarians: 81 (52.9%) women and 72 (47.1%) men. The average age of subjects was 83.9 ± 3.2 years. Mean total 25 hydroxyvitamin D concentration was 11.2 ± 7.0 ng/ml; 137 (89.5%) persons had vitamin D deficiency, 12 (7.8%) had insufficiency, and only 4 (2.6%) persons were vitamin D sufficient. Positive weak correlation between total 25 hydroxyvitamin D and ADL score (r = 0.2, p = 0.01) and very weak correlation between total 25 hydroxyvitamin D and IADL score (r = 0.19, p = 0.02) were found. Total 25 hydroxyvitamin D level was correlated with ADL score in women (r = 0.23, p = 0.04). In the 80–84 years group ADL score correlated with total 25 hydroxyvitamin D level (r = 0.23, p = 0.02). Conclusion The majority of investigated octogenarians had vitamin D deficiency. The level of vitamin D was associated with the ADL score. There was no association between the vitamin D level and the IADL score, although a weak correlation was found between vitamin D level and category of food preparation.